Effect of nutritional factors on the growth and production of biosurfactant by Pseudomonas aeruginosa strain 181 - Al-Araji, Laith Issa Yassin; Raja Abd Rahman, Raja Noor Zaliha; Basri, Mahiran; Salleh, Abu Bakar (Academy of Sciences Malaysia, 2008)
The growth and production of biosurfactant by P. seudomonas aeruginosa (181) was dependant on nutritional factors. Among the eleven carbon sources tested, glucose supported the maximum growth (0.25 g/L) with the highest biosurfactant yield and this was followed by glycerol. Glucose reduced the surface tension to 35.3 dyne/ cm and gave an E24 reading of 62.7%. Butanol gave the lowest growth and had no biosurfactant production. For the nitrogen sources tested, casamino acid supported a growth of 0.21 g/L which reduced the surface tension to 41.1 dyne/cm and gave an E24 reading of 56%. Soytone was assimilated similarly, with good growth and high biosurfactant production. Corn steep liquor gave the lowest growth and did not show any biosurfactant activity.